The Effect of Instructional Leadership School Principles, Teacher Innovation and Supervision in The Quality of Learning Management at Muhammadiyah Jakarta Senior High School - Yudha Prapanja; Armai Arief; Sopa Sopa (Asian Social Work Journal, 2023)
This study aims to determine the effect of instructional leadership, teacher innovation and supervision on the quality of learning management at SMA Muhammadiyah Jakarta. The location of the research was carried out at SMA Muhammadiyah South Jakarta. The research method used in this study was a survey method, with a population of 178 teachers with a sample of 123 teachers. The research instruments consist of learning management quality instruments, instructional leadership instruments, teacher innovation instruments and supervision instruments. The research results obtained (1) there is a positive direct effect of instructional leadership on the quality of learning management, (2) there is a positive direct effect of teacher innovation on the quality of learning management, (3) there is a positive direct effect of supervision on the quality of learning management, (4) there is a positive direct effect of instructional leadership on supervision, (5) there is a positive direct effect of teacher innovation on supervision, and (6) ) there is a positive direct effect of instructional leadership on teacher innovation. The implication of this research is that if you want to improve the quality of learning management, you must strengthen instructional leadership, teacher innovation and supervision. Suggestions that the quality of learning management is increased, all parties, namely the education office, school principals and the Muhammadiyah organization provide support for the research results that have been obtained.